Development Issues of the Balaton Region - Buday-Sántha, Attila (Discussion Papers, 2012)
The Author of the present study summarises his multi-decade research related to the Balaton region. He provides an extensive overview of the natural geographical, social and economic situation of the area from a historical perspective, including the evaluation of positive and negative impacts of the investments and developments. A special emphasis is placed on the future potential objectives, opportunities and methods of the development of the Balaton region. The book contains a detailed and concise summary of all the necessary information in this topic and provides valuable knowledge for researchers and all those interested in one of the largest lakes of Central and Eastern Europe.